The perceptual and biomechanical effects of scaling back exosuit assistance to changing task demands - Jinwon Chung; D. Adam Quirk; Jason M. Cherin; Dennis Friedrich; Daekyum Kim; Conor J. Walsh (Scientific Reports)
Abstract Back exoskeletons are gaining attention for preventing occupational back injuries, but they can disrupt movement, a burden that risks abandonment. Enhanced adaptability is proposed to mitigate burdens, but perceptual benefits are less known. This study investigates the perceptual and biomechanical impacts of a SLACK suit (non-assistive) controller versus three controllers with varying adaptability: a Weight-Direction-Angle adaptive (WDA-ADPT) that scales assistance based on the weight of the boxes using a chest-mounted camera and machine learning algorithm, movement direction, and trunk flexion angle, and standard Direction-Angle adaptive (DA-ADPT) and Angle adaptive (A-ADPT) controllers. Fifteen participants performed a variable weight (2, 8, 14 kg) box-transfer task. WDA-ADPT achieved the highest perceptual score (88%) across survey categories and reduced peak back extensor (BE) muscle amplitudes by 10.1%. DA-ADPT had slightly lower perceptual (76%) and peak BE reduction (8.5%). A-ADPT induced hip restriction, which could explain the lowest perceptual score (55%) despite providing the largest reductions in peak BE muscle activity (17.3%). Reduced perceptual scores achieved by DA and A-ADPT were explained by controllers providing too much or little assistance versus actual task demands. These findings underscore that scaling assistance to task demands improves biomechanical benefits and the perception of the device’s suitability.